Justice and Trust - Werhane, Patricia H. (Journal of business ethics, 1999)
With the demise of Marxism and socialism, the United States is becoming a model not merely for free enterprise, but also for employment practices worldwide. I believe that free enterprise is the least worst economic system, given the alternatives, a position I shall assume, but not defend, here. However, I shall argue, a successful free enterprise political economy does not entail mimicking US employment practices. I find even today in 1998, as I shall outline in more detail, these practices, when consistently carried out, by and large erode trust in the workplace, they are, on balance unfair to workers and managers, and, if Jeffrey Pfeffer is correct, they do not maximize long-term corporate earnings or growth. Getting clear on US employment practices and their weaknesses may help to shape other models for employment that neither contravene free enterprise nor are degrading to workers.